Autophagic degradation of peroxisomes in mammals. (11th April 2016) - Zientara-Rytter, Katarzyna; Subramani, Suresh
Abstract : Peroxisomes are essential organelles required for proper cell function in all eukaryotic organisms. They participate in a wide range of cellular processes including the metabolism of lipids and generation, as well as detoxification, of hydrogen peroxide (H2 O2 ). Therefore, peroxisome homoeostasis, manifested by the precise and efficient control of peroxisome number and functionality, must be tightly regulated in response to environmental changes. Due to the existence of many physiological disorders and diseases associated with peroxisome homoeostasis imbalance, the dynamics of peroxisomes have been widely examined. The increasing volume of reports demonstrating significant involvement of the autophagy machinery in peroxisome removal leads us to summarize current knowledge of peroxisome degradation in mammalian cells. In this review we present current models of peroxisome degradation. We particularly focus on pexophagy–the selective clearance of peroxisomes through autophagy. We also critically discuss concepts of peroxisome recognition for pexophagy, including signalling and selectivity factors. Finally, we present examples of the pathological effects of pexophagy dysfunction and suggest promising future directions.